Trickle or treat: The dynamics of nutrient export from polar glaciers. Issue 9 (13th March 2017) - Dubnick, Ashley; Wadham, Jemma; Tranter, Martyn; Sharp, Martin; Orwin, John; Barker, Joel; Bagshaw, Elizabeth; Fitzsimons, Sean
Abstract: Cold‐based polar glacier watersheds contain well‐defined supraglacial, ice‐marginal, and proglacial elements that differ in their degree of hydrologic connectivity, sources of water (e.g., snow, ice, and/or sediment pore water), meltwater residence times, allochthonous and autochthonous nutrient, and sediment loads. We investigated 11 distinct hydrological units along the supraglacial, ice marginal, and proglacial flow paths that drain Joyce Glacier in the McMurdo Dry Valleys of Antarctica. We found that these units play unique and important roles as sources and/or sinks for dissolved inorganic nitrogen and dissolved inorganic phosphorus and for specific fractions of dissolved organic matter (DOM) as waters are routed from the glacier into nutrient‐poor downstream ecosystems. Changes in nutrient export from the glacial system as a whole were observed as the routing and residence times of meltwater changed throughout the melt season. The concentrations of major ions in the proglacial stream were inversely proportional to discharge, such that there was a relatively constant "trickle" of these solutes into downstream ecosystems. In contrast, NO3 − concentrations generally increased with discharge, resulting in delivery of episodic pulses of dissolved inorganic nitrogen‐rich water ("treats") into those same ecosystems during high discharge events. DOM concentrations or fluorescence did not correlate with discharge rate, but high variability in DOM concentrations or fluorescence suggests that DOM may be exported downstream as episodic treats, but with spatial and/or temporal patterns that remain poorly understood. The strong, nutrient‐specific responses to changes in hydrology suggest that polar glacier drainage systems may export meltwater with nutrient compositions that vary within and between melt seasons and watersheds. Because nutrient dynamics identified in this study differ between glacier watersheds with broadly similar hydrology, climate, and geology, we emphasize the need to develop conceptual models of nutrient export that thoroughly integrate the biogeochemical and hydrological processes that control the sources, fate, and export of nutrients from each system.